Tinjauan Yuridis Wanprestasi dalam Perjanjian Utang Piutang: Studi Putusan Nomor 275/Pdt.G/2024/Pn Medan - Reza Farhansyah; Sylvia Elia Situmorang; Said Rizal; Rizki . (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Breach of contract in debt agreements is one of the most common civil disputes arising from the failure of a debtor to fulfill contractual obligations. This study aims to analyze the legal regulation of breach of contract in debt agreements, judicial considerations, and the juridical review of Decision Number 275/Pdt.G/2024/PN Medan. The research employs a normative juridical method using statutory, doctrinal, and case approaches. The results indicate that breach of contract is regulated under the Indonesian Civil Code, particularly Articles 1234, 1239 and 1243. The court found that defendant had committed a breach of contract by failing to fulfill a debt obligation that had become the responsibility of the debtor’s heir. The decision is consistent with civil law provisions, the principle of pacta sunt servanda, and legal certainty. The legal implication of this decision is that a deceased debtor’s obligations may still be claimed against the heirs insofar as they relate to the inherited estate.